Proyeksi Konsumsi Energi Industri Pengolahan di Bali Sampai Dengan Tahun 2050 Menggunakan Software LEAP - I Wayan Ambarayana; I. A. Dwi Giriantari; I Nyoman Setiawan (Program Studi Teknik Elektro UNUD, 2019)
Increasing energy demand with limited resources is an obstacle in supplying demand for electrical energy sources at this time. The solution to this problem becomes essential due to the planning of excessive energy supply, as well as planning that does not meet the energy demand will cause new problems on the side of energy production. Therefore accurate energy consumption forecasting is very important. In this study, the projected use of energy in the processing industry sector in Bali uses LEAP software using a database from 2015 to 2018. The use of fuels in the processing industry in Bali according to modeling results will continue to increase until 2050. This increase due to an increase in population resulting in increased demand for processing industry products so that the production of processing industries has increased which directly increases fuel consumption. This increase in production is also due to increased purchasing power, this is shown from the increase in per capita GRDP of Bali province which has increased until 2050. GRDP of the processing industry according to modeling results has increased until 2050 this is in accordance with the energy needs of the processing industry , where an increase in the production of the processing industry will also result in an increase in the GRDP of the processing industry